The Classification of Patients with Chronic Pain: Age and Sex Differences - Andrew J Cook; Dania C Chastain (Pain Research and Management)
OBJECTIVE: To further develop an empirically based classification system for chronic pain patients through the examination of age and sex differences, and incorporation of pain duration in the grouping algorithm.